ANALISIS RUGI-RUGI PADA SERAT OPTIK MENGGUNAKAN OTDR (OPTICAL TIME DOMAIN REFLECTOMETER) - Yussa Ananda (Jurnal Simetri Rekayasa, 2019)
Optical fiber is one of the transmission media that is widely used for local networks at this time, its use is predicted to replace copper cables. In practice, optical fiber itself has losses, including: losses caused by the fiber itself (intrinsic loss) such as Rayleigh Scattering, absorption loss, dispersion. There are also losses caused by external forces and human-error (extrinsic loss) such as losses on connectors/splices, coupling/splitter losses, and bending losses. Optical fiber is divided into single-mode and multi-mode. single-mode fibre uses smaller cores. As for what was used in this study, they are both. In this study, optical fiber losses were measured with OTDR (Optical Time Domain Reflectometer). Overall, based on the results of the comparative analysis of optical fiber losses from the results of measuring tools with empirical formula calculations, a large enough difference was obtained but not significant to deny the results of OTDR measurements in the field